Exploring fraud vulnerabilities in public sector promotions: An analysis through the lens of fraud hexagon theory and maqashid al-shari'ah - Cahyo Kurniawan, Pratomo; Nailul Izaty, Santi; Febriani, Fenti (JIFA (Journal of Islamic Finance and Accounting), 2025)
This research delves into gratification fraud in the Pemalang Regency Government's job auction process, employing the Fraud Hexagon Theory and the Maqoshid Syariah concept. The study aims to uncover triggers for gratification and assess its alignment with Islamic principles, ultimately contributing to more effective fraud prevention. Using a qualitative method with a case study approach, data was gathered through in-depth interviews, field observations, and document reviews. The Fraud Hexagon theory identified key elements driving fraudulent acts, while Maqoshid Syariah served as an evaluative framework against Islamic values. Findings reveal that gratification in Pemalang's job auctions stems from factors like external pressure, opportunities, rationalization, and individual capabilities. From a Maqoshid Syariah perspective, such gratifications are deemed detrimental, deviating from principles of justice and benefit. The study suggests that applying sharia principles can strengthen monitoring and prevent future gratification. Theoretically, this research advances fraud detection models by integrating Fraud Hexagon and Maqoshid Syariah, an underexplored area. Practically, it offers actionable policy insights for local governments and anti-corruption bodies to reform job auction systems with an ethical and Islamic approach